Evaluating the Cigarette Excise Moratorium through Qawāʿid Fiqhiyyah - Riki Maulana; Hasan Bisri; Muhammad Fauzan Januri; Agung Pardini (KEDJATI Foundation, 2026)
The government’s moratorium on cigarette excise tax increases reflects a persistent policy tension between maintaining economic stability and safeguarding public health. While the tobacco industry contributes significantly to state revenue and employment, its widespread consumption generates serious long-term health and social harms. This study employed a qualitative normative approach with a descriptive-analytical design. Data were derived from secondary sources, including government reports, academic literature, and classical as well as contemporary Islamic legal texts. The analysis was grounded in al-qawāʿid al-khamsah and their derivative legal maxims to assess the balance between maṣlaḥah and mafsadah. The findings indicate that the moratorium produces short-term economic benefits, including industrial stability, employment protection, and sustained fiscal revenue. However, it also leads to more significant long-term harms, such as increased cigarette consumption, patterns of isrāf, and rising public health burdens. From the perspective of qawāʿid fiqhiyyah, these harms outweigh the benefits when the policy is not accompanied by mitigating measures. This study concludes that a more balanced policy is required through gradual excise tax increases combined with transitional support for affected stakeholders, public health initiatives, and the development of alternative economic sectors. Such an approach aligns with the objectives of maqāṣid al-sharīʿah, particularly the protection of life and wealth, and offers a more sustainable and ethically grounded policy framework.